2020
DOI: 10.3389/fpsyt.2020.00448
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Mental Health Effects of a Devastating Wildfire Are Amplified by Socio-Demographic and Clinical Antecedents in Elementary and High School Staff

Abstract: Objectives: To assess the likely prevalence rates of Major Depressive Disorder (MDD), Generalized Anxiety Disorder (GAD) and Post-Traumatic Stress Disorder (PTSD) in staff of Fort McMurray School Districts eighteen months after a May 2016 wildfire, and to determine possible predictors. Methods: A quantitative cross-sectional survey was used to collect data through selfadministered online questionnaires to determine likely MDD, GAD and PTSD using well validated self-report questionnaires. Results: Of 1,446 staf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 50 publications
5
59
0
Order By: Relevance
“…Insufficient social support during the post-disaster period is associated with various psychological symptoms after the disaster ( 6 , 7 , 13 , 26 , 91 ), as well as disorders like PTSD ( 13 ) major depressive disorder (MDD) and prolonged grief disorder (PGD) ( 56 ). On the contrary, stronger social support resources have been related to greater resilience ( 18 ), which may function as a buffer against negative mental health effect of stressful events through influencing how people manage the situation ( 92 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Insufficient social support during the post-disaster period is associated with various psychological symptoms after the disaster ( 6 , 7 , 13 , 26 , 91 ), as well as disorders like PTSD ( 13 ) major depressive disorder (MDD) and prolonged grief disorder (PGD) ( 56 ). On the contrary, stronger social support resources have been related to greater resilience ( 18 ), which may function as a buffer against negative mental health effect of stressful events through influencing how people manage the situation ( 92 ).…”
Section: Resultsmentioning
confidence: 99%
“…• Support from family/friends following wildfires may be protective against likely PTSD, • A prior diagnosis of an anxiety disorder significantly increased risk for developing PTSD Agyapong et al (26) This study describes the changes in the stress, anxiety, and depression levels of subscribers to the Text4Hope program after 6 weeks of exposure to daily supportive SMS text messages.…”
Section: References Study Aims Methods Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…PM 2.5 levels exceeding the 24 h national standard of 35 μg/m 3 have been reported during wildfire events in southern California, with concentrations in some cases over 10 times (>230 μg/m 3 ) higher than background levels [ 19 , 20 ]. Importantly, wildfire impacts to individuals may be exacerbated depending on the socioeconomic characteristics of affected communities [ 14 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also reported links between wildfires and adverse mental health effects in adults and children, including increased symptoms of PTSD (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), increased symptoms of depression and anxiety (17,19,(23)(24)(25)(26)(27)(28), mental health difficulties (18,29,30), reduction in health and wellbeing (31), increased consumption of anxiolytics-hypnotics (32), and decreased capacity to cope with adversity (33). The combined adverse impacts of wildfire disasters on individuals' mental health and coping abilities, particularly in youth, are important because coping plays a major role in post-disaster recovery, and lack thereof can be detrimental to long-term mental health outcomes [also see (34)].…”
Section: Introductionmentioning
confidence: 99%